Dimensionless scalings of confinement, heat transport and pedestal stability in JET-ILW and comparison with JET-C. (18th October 2016) - Frassinetti, L; Saarelma, S; Lomas, P; Nunes, I; Rimini, F; Beurskens, M N A; Bilkova, P; Boom, J E; de la Luna, E; Delabie, E; Drewelow, P; Flanagan, J; et al.
Abstract: Three dimensionless scans in the normalized Larmor radius ρ *, normalized collisionality ν * and normalized plasma pressure β have been performed in JET with the ITER-like wall (JET-ILW). The normalized energy confinement and the thermal diffusivity exhibit a scaling with ρ * consistent with the earlier results obtained in the carbon wall JET (JET-C) and with a gyro-Bohm scaling. In the pedestal, experimental results show that the stability is not dependent on ρ *, qualitatively in agreement with the peeling–ballooning (P–B) model. The ν * dimensionless scaling shows that JET-ILW normalized confinement has a stronger dependence on collisionality than JET-C. This leads to a reduction of the difference in the confinement between JET-ILW and JET-C to ≈10% at low ν * . The pedestal stability shows an improvement with decreasing ν * . This is ascribed to the increase of the bootstrap current, to the reduction of the pedestal width and to the reduction of the relative shift between pedestal density and temperature position. The β dimensionless scan shows that, at low collisionality, JET-ILW normalized confinement has no clear dependence with β, in agreement with part of the earlier scalings. At high collisionality, a reduction of the normalized confinement with increasing β is observed. This behaviour is driven mainly by the pedestal where the stability is reduced with increasing β . The P–B analysis shows that the stability reduction with increasing β at high ν * is due to the destabilizing effect of the increased relative shift.